Knowledge, Attitude, and Practice toward Youth-Friendly Reproductive Health Services among Mizan-Tepi University Students, South-Western Ethiopia. (20th March 2022) - Getachew, Samuel; Abate, Lema; Asres, Abyot; Mandefro, Abel
Abstract : Background . Youth-friendly reproductive health services are designed to meet the unique needs of young individuals. Nevertheless, in developing countries such as Ethiopia, knowledge, attitude, and utilization of these services are very limited. This study was designed to assess the knowledge, attitude, and utilization of youth-friendly health services and associated factors among students. Method . A public university-based cross-sectional study was conducted between October and January 2019. Participants were chosen from the target group using a simple random selection procedure. To find the factors linked to youth-friendly health services, researchers used descriptive analysis, the chi-square test, and a logistic regression model. Result . This study revealed that 237 (55.4%), 256 (59.8%), and 262 (61.2%) students had no knowledge, negative attitude, and not practiced youth-friendly reproductive health services, respectively. The binary logistic regression results revealed that male students were more likely to have knowledge and practice (AOR = 1.847; 95% CI: 1.124, 3.034; p = 0.015 ) and (AOR = 1.821; 95% CI: 1.114, 2.975; p = 0.017 ) respectively; however, they had less likely positive attitudes (AOR = 0.519; 95% CI: 0.315, 0.856; p value = 0.010) compared to female students. Students from primary and above educated families were more likely to have knowledge, attitude, and practice compared to students from uneducated families. Conclusion . Overall, students' knowledge, attitudes, and utilization of youth-friendly reproductive health services were poor. As a result, additional efforts, such as the availability of service providers and the improvement of facilities, as well as education linked to the service for young people and the allocation of appropriate service time, are required.